High-throughput drone system for rice hoja blanca virus field screening - CGIAR Research Program on Rice (2021)
The system is going to be tested in the next screening season. Using drones can standardize screening of rice breeding lines. Images taken by drones can indicate which lines would have symptoms of the virus: They are lighter in color, nearly white. RHBV-resistant breeding lines, meanwhile, would be vivid green.